The pathological features of prostate cancer in South African men: what is the prevalence of local invasion at diagnosis? - Mathabe, Kgomotso Minah (My University, 2020)
Background Prostate cancer is the most common solid organ cancer amongst South African men. It poses a risk to life and is a significant public health burden. The management of patients affected by this disease who have access to tertiary hospitals includes a measurement of the serum prostate specific antigen level and a prostate biopsy. Data gathered from histology reports that are currently not used in the prognostication and risk stratification models have the potential to refine these tools. The prevailing view in current literature is that prostate cancer in Black men is more aggressive than in other races, and studies are being performed to determine the possible genetic basis for this. Methods A retrospective, observational, cross- sectional study of the histology reports of prostate biopsy specimens received by the NHLS from Charlotte Maxeke Johannesburg Academic Hospital from 01 January 2004 to 31 December 2009, which were positive for PCa, was conducted. Results-Histology reports on 726 biopsy specimens were available for assessment. Race and clinical data were not available. The histology reports are of a high quality. The majority of specimens came from by core needle biopsies using the systematic technique, which provided superior information when compared to the other techniques. The majority of patients presented with advanced disease as shown by a high PSA >20ng/ml in 70%, high-grade disease with Gleason grade ≥ 7= 4 + 3 and evidence of locally advanced disease in all but 3 specimens, specifically perineural spread in 54%. The majority of patients were in the 7th and 8th decade of life. Conclusion The quality of our histology reports is high and provides data that can be used to optimally risk stratify and prognosticate patients. The majority of patients in the study presented with advanced disease. The inaccessibility of clinical records and unavailable race data added a perspective to the understanding of PCa in this institution.
A research report submitted in partial fulfilment for the degree of MMed (Urology) to the Faculty of Health Sciences, School of Medicine, University of the Witwatersrand, Johannesburg, 2020